The taste for health: the role of taste receptors and their ligands in the complex food/health relationship - Morini, Gabriella (Frontiers in Nutrition, 2024)
Taste, food and health are terms that since always accompanied the act of eating, but the association was simple: taste serves to classify a food as good or bad and therefore influences food choices, which determine the nutritional status and therefore health. The identification of taste receptors, in particular the G protein-coupled receptors that mediate sweet, umami and bitter tastes, in the gastrointestinal tract has assigned them much more relevant tasks, from nutrient sensing and hormones release, to microbiota composition and immune response, to a rationale for the gut-brain axis. Particularly interesting are bitter taste receptors, since most of the times they do not mediate macronutrients (energy). The relevant roles of bitter taste receptors in the gut indicated that they could became new drug targets and their ligands new medication or components in nutraceutical formulation. Traditional knowledge from different cultures reported that bitterness intensity was a sort of indicator to distinguish plants used as food from those used as medicine and many non-cultivated plants were used to control glucose level and treat diabetes, modulate hunger and heal gastrointestinal disorders due to pathogens and parasites. This represent a means for the scientific integration of ancient wisdom with advanced medicine, constituting a possible boost also for more sustainable food and functional food innovation and design.